Orthodontic treatment alternative to a class III subdivision malocclusion - Guilherme Janson; José Eduardo Prado de Souza; Sérgio Estelita Cavalcante Barros; Pedro Andrade Junior; Alexandre Yudi Nakamura (University of São Paulo, 2009)
Class III malocclusions are considered one of the most complex and difficult orthodontic problems to diagnose and treat. Skeletal and/or dental asymmetries in patients presenting with Class III malocclusions can worsen the prognosis. Recognizing the dentoalveolar and skeletal characteristics of subdivision malocclusions and their treatment possibilities is essential for a favorable nonsurgical correction. Therefore, this article presents a nonsurgical asymmetric extraction approach to Class III subdivision malocclusion treatment which can significantly improve the occlusal and facial discrepancies.